2020
DOI: 10.3390/biomedicines8080246
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Spectrometry Based Proteome Comparison of Extracellular Vesicle Isolation Methods: Comparison of ME-kit, Size-Exclusion Chromatography, and High-Speed Centrifugation

Abstract: Extracellular vesicles (EVs) are small membrane-enclosed particles released by cells under various conditions specific to cells’ biological states. Hence, mass-spectrometry (MS) based proteome analysis of EVs in plasma has gained much attention as a method to discover novel protein biomarkers. MS analysis of EVs in plasma is challenging and EV isolation is usually necessary. Therefore, we compared differences in abundance, subtypes, and contamination for EVs isolated by high-speed centrifugation, size exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Since CD63, CD9, FLOT1 and HSC70 are enriched in Vn96 samples compared to ME and Scr samples, these findings suggest that Vn96 does not merely sediment circulating proteins at 17,000 × g under these conditions, but rather enriches for these EV-specific proteins. Recent publications have also demonstrated co-isolation of lipoproteins (ApoB and ApoA1) with both UCF and Vn96 15 , 27 , suggesting that the proteomic profile of material isolated by Vn96 may be similar to UCF.
Figure 2 Characterization of plasma EVs isolated by UCF, scUCF and Vn96 methods, all from the same donor plasma (n = 3).
…”
Section: Resultsmentioning
confidence: 94%
“…Since CD63, CD9, FLOT1 and HSC70 are enriched in Vn96 samples compared to ME and Scr samples, these findings suggest that Vn96 does not merely sediment circulating proteins at 17,000 × g under these conditions, but rather enriches for these EV-specific proteins. Recent publications have also demonstrated co-isolation of lipoproteins (ApoB and ApoA1) with both UCF and Vn96 15 , 27 , suggesting that the proteomic profile of material isolated by Vn96 may be similar to UCF.
Figure 2 Characterization of plasma EVs isolated by UCF, scUCF and Vn96 methods, all from the same donor plasma (n = 3).
…”
Section: Resultsmentioning
confidence: 94%
“…Common problems when isolating EVs from blood plasma and other biological fluids are co-isolation of albumin, lipoproteins and other non-EV proteins [ 40 ]. In a recent study, EV isolation from plasma using SEC and ultracentrifugation was compared.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, EV isolation from plasma using SEC and ultracentrifugation was compared. It was shown that SEC isolation resulted in higher yield and less contamination of albumin, but more lipoproteins compared to ultracentrifugation due to the overlap in size [ 40 ]. Similar to the blood plasma, lymphatic drainage fluid is a complex fluid which makes the isolation of pure EVs challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Vn96 isolates EVs with reduced contamination from protein aggregates or lipoproteins, compared to other methods of EV isolation (i.e. ultracentrifugation) ( 57 ) . Briefly, 1 ml of EV-containing media was incubated with 40 μl (2.5 mg/ml) of Vn96 for 1 h, rotating, at room temperature.…”
Section: Methodsmentioning
confidence: 99%